Guided Imagery untuk Menurunkan Social Appearance Anxiety pada Wanita Dewasa Awal Obesitas - Dharmariana, June Rodhian; Hamidah, Hamidah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2019)
Abstract Early adulthood is a period when individu face and should to be able to adjust changes, patterns of life and new hopes. Individu also have developmental tasks that must be completed and determine life in the period of further development. However, some early adult women have reported obesity which has an impact on social appearance anxiety. One form of therapy that can be used to reduce anxiety is guided imagery. This research is an experimental study with a single-group pretest / posttest design. The research subjects were 4 people who were determined through purposive sampling technique. Data collection was carried out using the social appearance anxiety scale compiled by Hart et al. (2008). This study used the non-parametric data analysis technique Wilcoxon signed-rank test. The analysis shows that guided imagery is not effective in reducing social appearance anxiety in early adult women who are significantly obese. Keywords: Guided Imagery, Social Appearance Anxiety, Early Adult Woman, Obesity. Abstrak Dewasa awal merupakan masa individu menghadapi dan dituntut mampu menyesuaikan diri terhadap perubahan, pola kehidupan dan harapan baru. Individu juga memiliki tugas perkembangan yang harus diselesaikan dan menentukan kehidupan di masa perkembangan selanjutnya. Namun demikian beberapa wanita dewasa awal dilaporkan mengalami obesitas yang berdampak pada kecemasan berpenampilan sosial atau social appearance anxiety. Salah satu bentuk terapi yang dapat digunakan untuk menurunkan kecemasan adalah guided imagery. Penelitian ini merupakan penelitian eksperimen dengan desain single-group pretest/posttest design. Subjek penelitian berjumlah 4 orang yang ditentukan melalui teknik purposive sampling. Pengumpulan data dilakukan menggunakan skala social appearance anxiety yang disusun oleh Hart, dkk. (2008). Penelitian ini menggunakan teknik analisis data non-parametrik wilcoxon signed-rank test. Hasil analisis menunjukkan bahwa pemberian guided imagery tidak efektif menurunkan social appearance anxiety pada wanita dewasa awal yang mengalami obesitas secara signifikan. Kata Kunci: Guided Imagery, Social Appearance Anxiety, Wanita Dewasa Awal, Obesitas.